2021
DOI: 10.1364/oe.430327
|View full text |Cite
|
Sign up to set email alerts
|

Dynamically stable single frequency ring resonator from diode pumped Nd:YAG modules with 55.6 W of output power

Abstract: A Nd:YAG rod single-frequency ring laser based on side-pumped commercial modules is presented. Thermally induced birefringence compensation was applied in a dynamically stable resonator providing 55.6 W of continuous, linearly polarized, TEM00 output. The particular case of a symmetric ring resonator containing one or two focusing rods and a pair of curved mirrors was analyzed and a design technique is presented, allowing for easy, continuous shaping of the stability limits by changing only the distances in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…If two laser rods positioned with a distance d close enougth so that d<<fmax and d<<fmin, (resonator scheme shown in Fig. 6), then similar equations are obtained [12,19]: From these equations we can note the design advantages of this kind of resonators: first, they are easy design equations, which directly link stability parameters with physical resonator parameters. Second, for a given stability parameters, there is no need to have a mirror or a lens with a specific focusing length.…”
Section: Symmetric Ring Dsrs With a Pair Of Curved Mirrors And Resona...mentioning
confidence: 85%
See 2 more Smart Citations
“…If two laser rods positioned with a distance d close enougth so that d<<fmax and d<<fmin, (resonator scheme shown in Fig. 6), then similar equations are obtained [12,19]: From these equations we can note the design advantages of this kind of resonators: first, they are easy design equations, which directly link stability parameters with physical resonator parameters. Second, for a given stability parameters, there is no need to have a mirror or a lens with a specific focusing length.…”
Section: Symmetric Ring Dsrs With a Pair Of Curved Mirrors And Resona...mentioning
confidence: 85%
“…The limit of the stability interval at maximum focal distance is fmax and the width of the stability zone is termed as ∆f=fmax-fmin. For a resonator with this geometry, the limits of the stability interval are given by [12,19]:…”
Section: Symmetric Ring Dsrs With a Pair Of Curved Mirrors And Resona...mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Yang et al [36] reported an 8 W diamond Raman CW laser that is continuously tunable across the range from 590 nm to 625 nm. Besides that, Bereczki et al [37] presented a Nd:YAG rod single-frequency ring laser in a dynamically stable resonator providing 55.6 W of continuous, linearly polarized, TEM 00 output. Depending on the nonlinear loss, the intracavity linear loss was precisely measured by recording the powers of the fundamental-wave and second-harmonic-wave lasers.…”
Section: Discussionmentioning
confidence: 99%
“…For maximum performance of resonators, fine tuning of the dynamic working point is required, and the possibility of performing this tuning was demonstrated for linear resonators with joined stability zones [5], asymmetric flat-flat mirrors [11] and symmetric ring lasers with a pair of curved mirrors [12].…”
Section: Introductionmentioning
confidence: 99%